Keputusan Mahasiswa Pengunjung Perpustakaan Menjadi Anggota UPU Perpustakaan Universitas Gadjah Mada: Decision of Students Visiting Gadjah Mada University Library to be Library Members - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract: The student's decision to be the member of a library is an expression of their need of information. This decision is influenced by internal and external factors, such as social, milieu and motivation. There are so many kinds of library in UGM: faculty, research center, diploma program, etc. That makes not all UGM students want to become the members of university library. The success of a library can be measured by the quantity and quality of its members, such as increasing of active users of potential users. The problems are: why do UGM students choose or do not choose to become the member of UPU library? What are the factors influenced this choice? Is there any significant difference between the sex, education, or development that they take? The method that is used is eclective qualitative and explanatory research, it explains causal relation between the variable through examining the explanation. The population are the visitors of UGM library, such as UGM students (D3, Si, Pascasarjana) and also from outside of UGM. The data are taken by quisioner, interview, and also examining some documents and similar research. Sample method is used to take 105 responds of library unit I in Bulaksumur and Unit 2 in Sekip. Majority of students have middle decision to become the member of the library. It means that according to them, a library is important for them, but it does not mean that this makes them to become the member of it although they feel that they can get some information from the book available. The research indicates that social factor, milieu and motivation together influence the students' decision to become the member of UPU UGM library. The milieu indicates by the support of every family to enforce the members of it to read more and more. And also the lecturers motivate the students to read more and more and to become the member of UPU UGM library. But the most variable that influence the students to become the member of UPU UGM library is their motivation to aquire their need of information and prestation.